The Relationship Between Coping Ability And Anxiety Levels In Pulmonary Tuberculosis Patients At Rantau Parapat General Hospital - Naibaho, Eka Nugraha V.; Tambunan, Rumondang; Silaban, Nataria Yanti; Siburian , Christine Handayani (Jurnal Kesehatan, Rekam Medis dan Farmasi (JUK-Medifa), 2023)
The inability of TB sufferers to carry out treatment can have an impact on the emergence of TB sufferers' concerns about their condition. The emergence of feelings of fear experienced by TB sufferers caused by their inability to carry out TB treatment properly will cause anxiety in TB sufferers. The purpose of the study was to determine the relationship between coping ability and anxiety levels in Pulmonary TB patients at Rantau Parapat General Hospital. Type of quantitative research with a cross sectional approach. The research was conducted at Rantau Parapat General Hospital in June-July 2021. The study population was 95 Pulmonary TB patients, The sampling technique in this study used Total Sampling, the study sample was 95 Pulmonary TB patients. Univariate and bivariate, bivariate data analysis techniques using Chi Square test. The results of the study There was a relationship between coping ability and anxiety levels in Pulmonary TB patients with a P-Value value of 0.001 <0.05. Advice as input to patients to continue to run Pulmonary TB treatment to get maximum treatment.